1998
DOI: 10.1021/tx9701743
|View full text |Cite
|
Sign up to set email alerts
|

Halide Effects in the Hydrolysis Reactions of (±)-7β,8α-Dihydroxy-9α,10α-epoxy-7,8,9,10-tetrahydrobenzo- [a]pyrene

Abstract: Rates of reaction of (+/-)-7beta,8alpha-dihydroxy-9alpha, 10alpha-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (DE-2) have been determined in 1:9 dioxane-water solutions containing 1.0 M KCl, 0.5 M KBr, and 0.1 M NaI over the pH range 4-13. These pH-rate profiles are more complicated than those for reaction of DE-2 in 0.2 M NaClO4 solutions and are interpreted in part by mechanisms in which halide ion attacks the diol epoxide as a nucleophile at intermediate pH, resulting in the formation of a trans-halohydrin. Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…Analysis of DNA from BaPtreated animals and from humans exposed to BaP indicates that the major adduct is produced by reaction with the (7R,8S,9S,10R)-enantiomer of BPDE (9,16). Hydrolysis of anti-BPDE produces predominantly transanti-BaP-tetraol (57). Taken together, these results indicate that trans-anti-BaP-tetraol should be the major isomer detected in urine, and our results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of DNA from BaPtreated animals and from humans exposed to BaP indicates that the major adduct is produced by reaction with the (7R,8S,9S,10R)-enantiomer of BPDE (9,16). Hydrolysis of anti-BPDE produces predominantly transanti-BaP-tetraol (57). Taken together, these results indicate that trans-anti-BaP-tetraol should be the major isomer detected in urine, and our results are consistent with this conclusion.…”
Section: Discussionsupporting
confidence: 89%
“…If the rate of ring-opening depended only on a H + , the data from all three acids would be the same. Although the rate of epoxide ring-opening is most strongly influenced by the protonation of the epoxide by H 3 O + , the rate of the reaction is also influenced by general acids (such as HSO 4 − ) donating a hydrogen to the epoxide oxygen and is increased by the presence of stronger nucleophiles than water, such as NO 3 − or SO 4 2− . , For solutions consisting of H 2 SO 4 and sodium sulfate (or any other sulfate salt), all three must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…At pH < ∼7 in 10:90 dioxane−water, 1 reacts with H + to form a triol carbocation 2 , which reacts with water to form trans 9,10- and cis 9,10-tetrols 3 and 4 in a 94:6 ratio. In this reaction, epoxide ring opening is rate-limiting, and carbocation 2 has a sufficient lifetime in water solutions to react with external nucleophiles such as azide and halide , ions.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that the covalent adducts from reaction of 5 with deoxyadenosine and with DNA have mostly cis 9,10-stereochemistry, whereas the covalent adducts from the reaction of diol epoxide 1 with DNA in the absence of chloride ion have mostly trans 9,10-stereochemistry. ,, There are significant cellular concentrations of chloride ion (∼10 mM), and therefore, chlorohydrin 5 may be formed from the reaction of diol epoxide 1 in vivo; thus, 5 may play a role in chemical carcinogenesis . At [Cl - ] = 10 mM, it can be calculated that ∼10% of carbocation 2 is trapped by chloride ion in water solution to form 5 …”
Section: Introductionmentioning
confidence: 99%